ANALISIS PENGARUH KUALITAS FINANSIAL PERUSAHAAN, KUALITAS AUDITOR, DAN KUALITAS PEREKONOMIAN TERHADAP OPINI AUDIT (GOING CONCERN) - , BAQARINA ULIE MIZANA HADORI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research described in this paper was designed to empirically examine the effects of financial and non-financial factors affecting issuance of goingconcern audit opinions by external financial auditors. Studies on factors affecting issuance of going-concern audit opinions have used various factors with results which are not conclusive. Therefore, these authors believe, further studies on this subject are still needed to enrich accounting literature. Financial fatctors included in this research are profitability, liquidity, solvability, an-nual sales growth, and growth of stock market price of the relevant auditee companies. Non financial factors included are quality of the relevant auditors and quality of the relevant economy. This study used 109 random sample of manufacturing companies listed in the Indonesia Stock Exchange in 2008-2012. Logistic regression analysis indicates that solvability, annual sales growth, and growth of stock market price significantly affect issuance of going-concern audit opinions by auditors. On the other hand, profitability, liquidity, quality of the auditors, and quality of the economy do not significantly affect issuance of going-concern audit opinions by auditors.